2022
DOI: 10.3389/fpsyg.2022.1013370
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the interplay between emotion regulation, self-efficacy, and L2 grit in higher education

Abstract: Teaching in higher education is critical and fraught with potential vicissitudes, which necessitates the presence of efficient professors armed with positive attributes to perform effectively. Although it is generally accepted that emotion regulation (ER) has numerous benefits for language teachers, in particular university professors, little is known about how it interacts with two other important constructs, i.e., self-efficacy and L2 grit. Furthermore, the effect of ER on L2 teacher grit has not been suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 94 publications
3
23
0
Order By: Relevance
“…This finding is in accord with those of Fathi et al (2020), Heydarnejad et al (2021a), Liu H. et al (2021), and Amirian et al (2022) as well as Xiyun et al (2022). Additionally, Cansoy et al (2020) and Zheng et al (2022) confirmed that teacher emotional wellbeing and self-efficacy beliefs are interrelated. According to the LTER model (Heydarnejad et al, 2021b), emotion regulation is the output of appraisal, attention deployment, situation modification, seeking social support, situation selection, and suppression.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This finding is in accord with those of Fathi et al (2020), Heydarnejad et al (2021a), Liu H. et al (2021), and Amirian et al (2022) as well as Xiyun et al (2022). Additionally, Cansoy et al (2020) and Zheng et al (2022) confirmed that teacher emotional wellbeing and self-efficacy beliefs are interrelated. According to the LTER model (Heydarnejad et al, 2021b), emotion regulation is the output of appraisal, attention deployment, situation modification, seeking social support, situation selection, and suppression.…”
Section: Discussionsupporting
confidence: 91%
“…According to the LTER model ( Heydarnejad et al, 2021b ), emotion regulation is the output of appraisal, attention deployment, situation modification, seeking social support, situation selection, and suppression. When teachers use effective emotion regulation strategies, the better they can manage and modify their emotional experiences ( Li et al, 2022 ; Zheng et al, 2022 ). Effective emotion regulation can affect teachers’ sense of efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Learners’ L2 grit is an amalgamation of perseverance of attempt and passion for long-term goals. Previous studies in the realm of grit reflected that this construct is significantly related to other teacher and student-related constructs, leading to the success of education (Shafiee Rad & Jafarpour, 2022 ; Steinmayr et al, 2018 ; Sudina et al, 2021 ; Sudina & Plonsky, 2021 ; Vadivel & Beena, 2019 ; Zheng et al, 2022 ). More specifically, the success of students in language learning is highly dependent on their effort and their passion for long-term goals; thus, L2 grit and its contribution to language assessment and academic achievement are of great importance.…”
Section: Introductionmentioning
confidence: 99%